Deanxit and tandospirone relieved unexplained limb edema in a depressed pituitary adenoma survivor: A case report - Dong, Xingyu; Fang, Sheng; Li, Wei; Li, Xuemei; Zhang, Sunfu (Frontiers in Psychiatry, 2022)
Our case report describes a 45-year-woman who suffered from limb edema for two months. Based on her pituitary adenoma history, we focused on tumor recurrence and other common potential diseases. However, none of the examinations showed any abnormality. We noticed her continuous complaints about her family relationship and existing depressed mood, and a psychiatry consultation was performed. She was diagnosed with major depressive disorder. After several days of Deanxit and Tandospirone treatment, the patient’s limb edema dramatically subsided. This case describes limb edema associated with depression for the first time. It highlights the importance of awareness of mental illness for non-psychiatrist, especially in patients with severe somatic symptoms but negative results.